2009
DOI: 10.1109/tip.2009.2028259
|View full text |Cite
|
Sign up to set email alerts
|

Principal Neighborhood Dictionaries for Nonlocal Means Image Denoising

Abstract: We present an in-depth analysis of a variation of the nonlocal means (NLM) image denoising algorithm that uses principal component analysis (PCA) to achieve a higher accuracy while reducing computational load. Image neighborhood vectors are first projected onto a lower dimensional subspace using PCA. The dimensionality of this subspace is chosen automatically using parallel analysis. Consequently, neighborhood similarity weights for denoising are computed using distances in this subspace rather than the full s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(128 citation statements)
references
References 32 publications
0
126
0
2
Order By: Relevance
“…Denoising is achieved by averaging pixel values weighted by the similarity of neighborhoods of each pixel in an image (Tasdizen, 2009). The conventional similarity weight is a degree of the similarity between neighborhoods of each pixel in an image (Yousif and Ban, 2014).…”
Section: Similarity Weight Image For Change Detectionmentioning
confidence: 99%
“…Denoising is achieved by averaging pixel values weighted by the similarity of neighborhoods of each pixel in an image (Tasdizen, 2009). The conventional similarity weight is a degree of the similarity between neighborhoods of each pixel in an image (Yousif and Ban, 2014).…”
Section: Similarity Weight Image For Change Detectionmentioning
confidence: 99%
“…Weighted Euclidean distance between two patches at one line (NLM-Pa using sum of invariant lines), see (22) …”
Section: L2mentioning
confidence: 99%
“…The window Ω x is called the search window at x and, for simplicity and faster computations, in [1] a choice of a square shape of fixed size is made while, according to authors, the search window should cover the entire image plane, hence the non-local nature of the algorithm. However, it has been reported that using for NLM a neighborhood instead of the whole image plane allows to increase the denoising performance [12,13,21,22], see also the discussion in [9] and the specific study in [19] where it is experimentally established that the optimal window size D is very small, when using a variant of the pixelwise NLM. As this present article will establish the best parameters, it will give an answer for the original pixelwise NLM.…”
Section: Introductionmentioning
confidence: 99%
“…Similar speed-ups could be achieved for NLM reconstructions. Additional software approaches, for example, methods proposed previously (53,54), can be used in order to speed up computation of the weights for the reconstruction by selectively choosing the neighborhoods within the search window.…”
Section: Computation Timementioning
confidence: 99%